Use of and short-term impacts of new cycling infrastructure in inner-Sydney, Australia: a quasi-experimental design. Issue 1 (December 2015) - Rissel, Chris; Greaves, Stephen; Wen, Li; Crane, Melanie; Standen, Chris
Abstract Background Given increasing investment in new cycling infrastructure, it is important to understand its impacts. The Sydney Transport and Health Study evaluates a new 2.4 km bi-directional separated bicycle path in inner-Sydney. This paper describes the users of the new bicycle path, and examines its short-term impacts upon cycling behaviour and perceptions of the local environment. Methods Data were collected from two bike counts at two intersections on the new bicycle path in the intervention area in 2013 and 2014. On-line surveys collected individual participant data in the intervention area and a similar comparison area before the bicycle path was built (2013), and 12 months later (four months after completion) (n  = 512). The data included self-reported cycling behaviour, use of the new bicycle path and perceptions of changes in the local environment. Results Bike counts at two sites on the new bicycle path reported an increase of 23 % and 97 % respectively at 12 months. However, among the participants in the cohort, there was no change in the self-reported weekly frequency of cycling. One in six (approximately 15 %) participants reported using the new bicycle path, with most users (76 %) living in the intervention area. Bicycle path users were most likely to be frequent riders (at least weekly) [adjusted odds ratio (AOR) = 7.50, 95 % CI 3.93–14.31], be a high intensity recreational rider (AOR = 4.38, 95 % CI 1.53–12.54) or a low intensity transport rider (AOR = 2.42, 95 % CI 1.17–5.04) and live closer to the bicycle path (AOR = 1.24, 1.13–1.37). Perceptions that the neighbourhood was more pleasant, that there were more people walking and cycling were significantly higher in the intervention area at 12 months (bothP values <0.05). Conclusions Existing cycling behaviour and proximity to the bicycle path were associated with the use of the new bicycle path. Increased use of the new bicycle path as reported by the participants in the intervention area and increased cycling recorded by the bike counts may be due to existing cyclists changing routes to use the new path, and more cyclists from outside the study area using the new path, as study participants did not increase their frequency of cycling. Increases in cycling frequency in the intervention neighbourhood may require a longer lead time, additional promotional activities and further maturation of the Sydney bicycle path network. Key message Understanding how new cycling infrastructure impacts communities can influence the promotion of such infrastructure.